Tertiary structural changes of the alpha-hemolysin from Staphylococcus aureus on association with liposome membranes - Bortoleto, R. K.; de Oliveira, AHC; Ruller, R.; Arni, R. K.; Ward, R. J. (Academic Press Inc., 1998)
The interaction of alpha-hemolysin (also called alpha-toxin) from Staphylococcus aureus with mixed egg-yolk phosphatidylcholine/cholesterol liposomes has been investigated using the intrinsic tryptophan fluorescence emission (ITFE) signal. The ITFE intensity of alpha-hemolysin, which was obtained using a novel purification protocol, showed a triphasic increase on incubation with liposomes at low protein/lipid ratios. The first, rapid phase results in an increase in ITFE of 10%, which reflects rapid conformation changes in the alpha-hemolysin on association with the liposome membrane, the second phase of the ITFE increase is associated with a red shift from 334 to 339 nm in the maximum emission wavelength, suggesting the transition to a partially unfolded intermediate in the oligomerization process. The third phase of the ITFE intensity change demonstrates a temporal correlation with the appearance of SDS-stable oligomers. The results demonstrate the feasibility of identification of intermediate protein conformations in complex membrane-associated processes by manipulation of the liposomal membrane composition. (C) 1998 Academic Press.
Keywords: alpha-hemolysin; alpha-toxin; Staphylococcus aureus; pore-forming; liposome membrane; unfolded intermediate